p21-activated kinase interacts with Wnt signaling to regulate tissue polarity and gene expression - Goh, Kah Yee; Ng, Natalie Weili; Hagen, Thilo; Inoue, Takao (Proceedings of the National Academy of Sciences - PNAS, 2012)
Wnt signaling is mediated by three classes of receptors, Frizzled, Ryk, and Ror. In Caenorhabditis elegans, Wnt signaling regulates the anterior/posterior polarity of the P7.p vulval lineage, and mutations in lin-17/Frizzled cause loss or reversal of P7.p lineage polarity. We found that pak-1/Pak (p21-activated kinase), along with putative activators of Pak, nck-1/Nck, and ced-10/Rac, regulates P7.p polarity. Mutations in these genes suppress the polarity defect of lin-17 mutants. Furthermore, mutations in pak-1, nck-1, and ced-10 cause constitutive dauer formation at 27 °C, a phenotype also observed in egl-20/Wnt and cam-1/Ror mutants. In HEK293T cells, Pak1 can antagonize canonical Wnt signaling. Moreover, overexpression of Ror2 leads to phosphorylation of Pak1. Together, these results indicate that Pak interacts with Wnt signaling to regulate tissue polarity and gene expression.